Mali : Second Review Under the Poverty Reduction and Growth Facility, Second Annual Program, and Requests for Augmentation and for Extension of Arrangement and Commitment Period. (IMF Staff Country Reports; Country Report ;, 2001)
After a sustained economic growth in the post-devaluation period, the Malian economy experienced severe crisis in the cotton sector that resulted in slow economic activity, low government revenue, and high external sector deficit. Executive Directors suggested that the successful diversification of the Malian economy would require efforts to develop human capital, physical infrastructure, and lower energy costs. They agreed that Mali has successfully completed the second review under the Poverty Reduction and Growth Facility Arrangement, and approved the waiver and extension for arrangement.